An Eeconomic Analysis Study for the Rehabilitating and Operating of Medical Bottles Factory in Anbar Governorate - Al Fahdawi , Khamees Khalif Mousa; Kadhem, Ryadh Jawad; Ali , Mahmoud Abdel Mohsen (Journal of Ecohumanism, 2025)
The study aims to measure and analyze the economic and social traces to the idea of rehabilitating and operating the medical bottles factory in Anbar Governorate. From this point, the significance of the study is derived to investigate the socio-economic returns based on the process of rehabilitating and operating the medical bottles factory in Anbar Governorate. The results show the socio-economic feasibility criteria used: financial profit, return of one dinar, unit costs of production, profit margin, rate of return on invested capital, payback period, break-even point, net present value, internal rate of return, added value, employment rate, the rate of employment, utilization and savings of foreign exchange) positive, encouraging and supportive results for the process of initiating the rehabilitation and operation of the mentioned factory.